2009
DOI: 10.1021/ol902050m
|View full text |Cite
|
Sign up to set email alerts
|

Selective Synthesis of 1-Functionalized-alkyl-1H-indazoles

Abstract: An efficient method for the selective "N1" alkylation of indazoles is described. Use of alpha-halo esters, lactones, ketones, amides, and bromoacetonitrile provides good to excellent yield of the desired N1 products.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
31
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(31 citation statements)
references
References 13 publications
0
31
0
Order By: Relevance
“…Uncatalyzed direct alkylation of indazoles is well known in the literature. [92][93][94][95] [96] Six years later in 2012, another phase transfer catalyzed direct method for alkylation of indazole was developed by Chandramouli et al In this process, 5cyano 1H-indazole (33 a) was alkylated by heating at 60°C with alkyl chloride in presence of K 2 CO 3 as a base and (Bmim)BF 4 as a phase transfer catalyst in ethyl acetate to achieve N-1 alkylated 1H-indazole derivative (33 b) as a major product (88%) and N-2 alkylated 2H-indazole derivative (33 c) as a minor product (12%) (Scheme 33). [97] Yu et al explored a new microwave-assisted, metal-free, green method for N-alkylation of indazoles with vinylpyridines in water.…”
Section: Alkylationmentioning
confidence: 99%
“…Uncatalyzed direct alkylation of indazoles is well known in the literature. [92][93][94][95] [96] Six years later in 2012, another phase transfer catalyzed direct method for alkylation of indazole was developed by Chandramouli et al In this process, 5cyano 1H-indazole (33 a) was alkylated by heating at 60°C with alkyl chloride in presence of K 2 CO 3 as a base and (Bmim)BF 4 as a phase transfer catalyst in ethyl acetate to achieve N-1 alkylated 1H-indazole derivative (33 b) as a major product (88%) and N-2 alkylated 2H-indazole derivative (33 c) as a minor product (12%) (Scheme 33). [97] Yu et al explored a new microwave-assisted, metal-free, green method for N-alkylation of indazoles with vinylpyridines in water.…”
Section: Alkylationmentioning
confidence: 99%
“…The selective alkylation of the N ‐1 position remains a challenge, specifically for C 3 ‐unsubstituted indazoles (16). It has been previously reported that use of potassium carbonate as a base yielded 92:1 ratio of N ‐1 versus N ‐2‐alkylated indazole derivatives (17). Moreover, the portion of N ‐2‐alkylated products is highly dependent on the bulkiness of the substituent at C 3 position as exemplified through N ‐1 versus N ‐2 ratio of 65:35 (when C 3 =‐H) as opposed to the corresponding ratio of 95:5 (when C 3 =4‐fluorophenyl) (18).…”
Section: Chemistrymentioning
confidence: 99%
“…A potentially more productive approach to 2-alkenyl-2 H -indazole targets begins with alkylation of indazole with α-bromocarbonyl compounds (path (c), Scheme 1). The major difficulty associated with this process is that N -1 thermodynamic alkylation products predominate in reactions run under most basic conditions [18]. Fortunately, the results of recent studies in this area show that 2 H -indazoles are generated through gallium/aluminium- and aluminium-mediated direct regioselective alkylation reactions of an indazole with α-bromocarbonyl compounds [19].…”
Section: Introductionmentioning
confidence: 99%